An analysis of the Chief Financial Officer function in Commonwealth organisations : benchmarking study - Australian National Audit Office (Canberra : Australian National Audit Office, 2001)
This benchmarking study examined Commonwealth CFO's roles and responsibilities in undertaking aspects of financial management and financial accounting activities within their organisation.
"Audit team: Ben Sladic, Samantha Montenegro, Tracey Martin, Richard Rundle"--P. 4.
Includes index.
Includes bibliographical references.
Also available in an electronic version via the Internet at http://www.anao.gov.au
Keywords: Finance, Public -- Australia -- Accounting; Chief financial officers -- Australia -- Auditing; Executive departments -- Australia -- Finance -- Management